The attitude of the People of the Book on Abrogation, and the Responses of Qur’anic Commentators: A comparative study - Alyoubi, Roaa Hameed; Al-Eid, Sulaiman Qasim (Journal of Islamic Sciences, 2025)
This study explores the stance of the People of the Book regarding abrogation, and the responses of Quranic commentators to their arguments. It does so by examining the positions of Jews and Christians on abrogation, analyzing the refutations presented in Quranic exegeses, deducing their methodological approaches, and comparing them."The study is divided into an introduction and two main sections:Section One: The doctrine of Jews and Christians regarding abrogation in the Torah and the Gospel. Section Two: The responses of Quranic exegetes to the stance of Jews and Christians on abrogation.Key findings include: Jews unanimously reject the abrogation of their law by a later prophet's teachings, though they disagree on its permissibility rationally and scripturally.Christians share this stance with Jews. The Quranic commentators refuted their arguments using scriptural evidence, including proofs from the Torah and the four Gospels - demonstrating that the Jewish and Christian scriptures themselves contain numerous instances of abrogation - as well as rational arguments, with Al-Razi particularly excelling in and extensively developing the latter approach.
Keywords: Jews; Christians; Abrogation; Quranic commentators